Factors Affecting Green Agricultural Production Financing Behavior in Heilongjiang Family Farms: A Structural Equation Modeling Approach - Wang, Hongli; Zhong, Shen; Guo, Jinguang; Fu, Yu (Frontiers in Psychology, 2021)
Adhering to large-scale agricultural operation is one of the basic ways to develop green agriculture, and it is also an inevitable choice for the development of modern agriculture in the country. Among them, as a major agricultural production province in China, the development of family farms in Heilongjiang Province has a significant impact on green agriculture. Based on the Theory of Planned Behavior, this paper takes the 222 family farm demonstration farms evaluated in Heilongjiang Province in 2019 as samples, and constructs a Structural Equation Model to discuss the influence of family farms’ participation in green agricultural production financing behavior in depth on the basis of directional design, distribution, recycling and sorting out questionnaires. The research found that the farmers’ financing willingness is determined by the family farm manager’s attitude, subjective norms and perceived behavior system, and the farmers’ financing willingness and perceived behavior control are determined by the farmers’ financing behavior. Among them, attitudes, subjective norms and perceived behavior control have significant positive impact on financing intention, and have a further effect on financing behavior. Financing willingness and perceived behavior control have a direct effect on financial behavior and have a significant positive effect on it. This article aims to improve and enhance the financing environment for family farms to participate in green agriculture, so as to increase the enthusiasm of the new agricultural operators to participate in green agriculture.